Top Research Priorities in Quantum Computing - Hatay, E.S.; Golec, M.; Nguyen, H.T.; Gill, S.S.; Patros, P.; Xu, M.; Buyya, R. (Elsevier, 2025)
Quantum computing is poised to revolutionize computational performance and capabilities, offering unprecedented efficiency in solving complex problems that surpasses classical approaches. This potential is particularly evident in fields such as optimization and artificial intelligence. This chapter delves into critical priority areas in quantum computing, including the development and application of quantum software tools. We place a strong emphasis on reimagining the use of quantum computing for modeling and simulation, sensing, and secure communication. Furthermore, we explore current trends like quantum communications for 6G networks, quantum cloud and serverless computing, scalable qubit arrays, and the pursuit of robust and reliable quantum systems. Lastly, we address emerging research areas and the open challenges ahead, encompassing advancements in foundational theory, education, ethical and societal considerations, and pathways to commercialization. © 2025 Elsevier B.V., All rights reserved.
Keywords: Interdisciplinary Research; Quantum Artificial Intelligence; Quantum Cloud Computing; Quantum Computing; Quantum Machine Learning; Quantum Secure Communication; Research Priorities